DINAMIKA PERKEMBANGAN BUSANA PENGANTIN ADAT BUGIS BULUKUMBA - Hasrani, Hasrani; Nahriana; Andi Hudiah (UNM Journal of Technology and Vocational, 2024)
This research aims to; (1) Know the traditional wedding process in Tanah Lemo Village, Bonto Bahari District, Bulukumba Regency; (2) Knowing the description of bridal clothing in Tanah Lemo Village, Bonto Bahari District, Bulukumba Regency; (3) Knowing the community's views on the dynamics of fashion development in Tanah Lemo Village, Bonto Bahari District, Bulukumba Regency. This type of research is a qualitative method using data collection, namely observation, interviews, documentation. The author tries to convey the object being discussed according to the reality that occurs in society. The results of the research show that the wedding customs of the Bulukumba Bugis tribe generally consist of several stages, namely 1) Ma'bici'bici, Mappanai doi', Barazanji, Mappacing, Cidong Buting, Marolla, Macelleng bisang. 2) The development of modern bodo wedding clothing now has various colors and shapes of clothing and accessories which no longer focus on colors according to heredity because they have followed the times.3) Providing understanding to the public that marriage traditions/customs which are still well maintained in the life of the Bugis community have noble values and teachings that are in line with Islamic values and teachings.   Keywords: Bodo clothes, Wedding customs, Bridal fashion.